The use of information technology in meeting instructional needs for special education - Yusuf, Byabazaire; Singh, Diljit (BritishJournal Publishing, 2012)
Information technology (IT) is now widely available in many countries, particularly in Malaysian schools, to assist special education teachers in many ways.However, the available literature worldwide suggests that most preparatory programs for teachers do not sufficiently equip them with IT skills.This study investigated the use of IT in meeting instructional needs for special education curriculum. The study explored the main curriculum domains for special teachers’ instructional needs, analyzed their current level of computer and IT knowledge and its usage in meeting their teaching needs.A mixed-method approach using questionnaires and interviews was used in the study. Questionnaires were sent to 120 special education professionals in 15 schools and education centers in Selangor, Malaysia.The findings indicate that the cognitive and communication domains were the principal areas for instructional needs.Professionals in supporting roles expressed a desire for a significant amount of IT based resources for the communication domain (p<0.05).Knowledge of the World Wide Web was statistically significant among female professionals, those in supporting roles, and Bachelor’s or Master’s degree holders (p<0.05).Current usage of IT-based resources indicated that the World Wide Web was quite significant among female professionals and those in supporting roles (p<0.05).Professionals with Bachelor’s or Master’s degrees also reported current usage of the World Wide Web and online databases as significant. Foresighted education managers could plan for clear future guidelines for providing the right IT infrastructure; systematic and regular IT training programs as well as reliable technical support services for their teaching staff.